2020
DOI: 10.3390/antiox9121176
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Fucoxanthin on High Glucose- and 4-Hydroxynonenal (4-HNE)-Induced Injury in Human Retinal Pigment Epithelial Cells

Abstract: The incidence of diabetes mellitus is increasing due to the eating and living habits of modern people. As the disease progresses, the long-term effects of diabetes can cause microvascular disease, causing dysfunction in different parts of the body, which, in turn, leads to different complications, such as diabetic neuropathy, diabetic nephropathy, and diabetic retinopathy (DR). DR is the main cause of vision loss and blindness in diabetic patients. Persistent hyperglycemia may cause damage to the retina, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Although Ang II receptor blockers, angiotensin converting enzyme inhibitors, diuretics and β-blockers are used to clinically treat pathological cardiac remodeling and heart failure, these drugs are not effective in reversing heart failure [ 36 ]. It has been reported that many carotenoids, such as fucoxanthin [ 37 ], lycopene [ 38 ] and neoxanthin [ 39 ], act as antioxidants. Lutein, which is an essential carotenoid, has a protective effect against oxidative stress and inflammation [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Ang II receptor blockers, angiotensin converting enzyme inhibitors, diuretics and β-blockers are used to clinically treat pathological cardiac remodeling and heart failure, these drugs are not effective in reversing heart failure [ 36 ]. It has been reported that many carotenoids, such as fucoxanthin [ 37 ], lycopene [ 38 ] and neoxanthin [ 39 ], act as antioxidants. Lutein, which is an essential carotenoid, has a protective effect against oxidative stress and inflammation [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors also reported that this carotenoid administered topically in RHS attenuated ethanol-induced skin inflammation through an increase in filaggrin expression [281]. As regards ocular diseases, FX protected ARPE-19 cells against high glucose-induced diabetes retinopathy in ARPE-19 cells via up-regulation of Nrf2 and reduction in apoptosis [282].…”
Section: Fucoxanthin 451 In Vitro Studiesmentioning
confidence: 85%
“…After the treatments, the cells were fixed in 4% paraformaldehyde (Sigma-Aldrich) for 10 minutes at room temperature, treated with 0.5% Triton X-100 in PBS for 10 minutes, and then blocked with 5% bovine serum albumin (BSA for 30 minutes at room temperature), following with previous study [ 25 ]. The cells were then incubated with anti-MMP-2 (1:200, Abcam) or anti-MMP-9 (1:200, Santa Cruz Biotechnology, Santa Cruz, CA, USA) diluted in 5% BSA overnight at 4 °C, followed by Alexa Fluor 448-goat anti-rabbit Immunoglobulin or Alexa Fluor 546-goat anti-mouse Immunoglobulin antibodies (Thermo Fisher Scientific, Waltham, MA, USA) for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%